2011
DOI: 10.1007/s00280-011-1692-y
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast attenuates side effects of cisplatin including testicular, spermatological, and hormonal damage in male rats

Abstract: In the current study, the protective effect of montelukast (ML) on cisplatin induced reproductive toxicity in rats was investigated. Twenty-eight rats were equally divided into four groups; first group was kept as control. In the second group, ML was orally administered at the dose of 10 mg/kg/day for 10 days. In the third group, CP was intraperitoneally administered at the dose of 7 mg/kg a single injection, and in fourth group, CP and ML were given together at the same doses. Although CP induced oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 26 publications
9
53
1
2
Order By: Relevance
“…Also more recently, we reported that the reproductive toxicity caused by CP may be prevented by montelukast treatment. 17 All of the investigations mentioned above encouraged us to plan this experimental design for the first time. In this context, in order to determine the beneficial effects of montelukast that is protective or therapeutic against CP toxicity, montelukast must be given both after and before CP injections.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Also more recently, we reported that the reproductive toxicity caused by CP may be prevented by montelukast treatment. 17 All of the investigations mentioned above encouraged us to plan this experimental design for the first time. In this context, in order to determine the beneficial effects of montelukast that is protective or therapeutic against CP toxicity, montelukast must be given both after and before CP injections.…”
Section: Discussionmentioning
confidence: 99%
“…17,[26][27][28] One of its most frequent and serious side effects is nephrotoxicity, which is described as acute tubular necrosis (ATN). Although the mechanisms of CP-induced nephrotoxicity are not fully understood, one mechanism of this toxicity is believed to involve ROS generation and inflammatory machine in the pathophysiology of CP-induced ATN after even a single dose of the drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies also showed that ML has a significant antioxidative effect on inhibition of lipid peroxidation in some tissues such as testis and liver 9,10 . Cuciureanu et al 11 demonstrated a partial hepatoprotective effect of montelukast against carbon tetrachloride induced hepatopathy on rats.…”
Section: Montelukast (Ml) Is An Anti-inflammatory Drugmentioning
confidence: 99%